The Role of Forensic Anthropology in Identifying and Investigating Altitude-Related Fatalities in Remote Mountainous Regions of Makassar, Indonesia - Susanto, Maghfirah; Muhammad Hasan (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Altitude-related fatalities pose significant challenges in remote mountainous regions due to harsh environments, limited accessibility, and postmortem changes. Forensic anthropology plays a pivotal role in identifying victims, determining the cause and manner of death, and aiding investigations. This study aimed to explore the contribution of forensic anthropology in investigating altitude-related deaths in the challenging terrain of Makassar, Indonesia. Methods: A retrospective analysis was conducted on 35 cases of altitude-related fatalities in the mountainous regions of Makassar between 2018 and 2023. Data were collected from forensic reports, autopsy records, and scene investigations. Anthropological methods, including skeletal analysis, postmortem interval estimation, and trauma analysis, were employed to aid in identification and death investigations. Results: The majority of victims were male (80%), with an average age of 32 years. The most common causes of death were falls (45.7%), followed by hypothermia (28.6%) and avalanche/landslide (14.3%). Postmortem interval estimation was challenging due to environmental factors, with a mean interval of 5.3 days. Anthropological analysis assisted in identifying 91.4% of the victims, even in cases with advanced decomposition or skeletal remains. Conclusion: Forensic anthropology is indispensable in identifying and investigating altitude-related fatalities in remote mountainous regions. Anthropological techniques contribute significantly to victim identification, cause and manner of death determination, and the reconstruction of events, assisting legal authorities and providing closure to families.